Validation of Molecular Typing for Endometrial Screening Test That Predicts Benign and Malignant Lesions - Tuo, Xiaoqian; Zhao, Lanbo; Wang, Qi; Han, Lu; Wang, Yiran; Ma, Sijia; Feng, Xue; Li, Qing; Sun, Chao; Wang, Qing; Shi, Guizhi; Hou, Huilian; et al. (Frontiers in Oncology, 2019)
The aim of this study is to examine the immunocytochemical expression of p53, Ki-67, and CA125 in endometrial brush samples for endometrial cancer. Forty-four patients were recruited with liquid-based cytology preparations during a 5-month period. Both the histological and cytological samples were assessed by histology based on hematoxylin and eosin (H&E), and the expression of p53, CA125, and Ki-67 in endometrial cells was examined by immunocytochemistry. The percentage and intensity of endometrial cells were scored on a scale of 0–3. The final score was calculated by the addition of all partial scores, and then Probit model was used to predict the possibility for malignant lesions. The mean immunoreactivity score of the three immunocytochemical biomarkers (p53, CA125, and Ki-67) in the positive group (including atypical hyperplastic cells and malignant cells) was significantly higher than in the negative group (benign cells and non-atypical hyperplastic cells). The possibility value of the positive group was also significantly higher than the negative group (P < 0.05). The cutoff value of the possibility value was 0.754, the sensitivity and specificity of which were 86.4 and 95.5%. The assessment of p53, CA125, and Ki-67 combined with the prediction model is valuable for the detection of endometrial cancer and atypical hyperplasia in endometrial cytology.